Registrering och avel för brunstvisningsförmåga hos mjölkkor - Fernqvist, Therese (2009)
Dairy farmers using artificial insemination (AI) are dependent on effective oestrus detection. In Sweden, AI is used for a majority of all dairy cows and oestrus synchronisation with hormones is not allowed. There are reports of declining ability to express oestrus with higher levels of milk production. This makes oestrus detection more difficult. Several aids for oestrus detection have been developed, for instance pedometers and mounting detectors. These aids can be used in loose housing systems and even though they can be very efficient, visual observations are still important for detection of possible missed or false registrations. Analysis of milk progesterone can be used to verify that an ovulation has occurred. Flooring and temperature influence the expression of oestrus. Lactation number, milk production, loose housing or tied system, season and feeding are examples of other factors that can influence oestrus expression. The chance of getting a cow pregnant seems to increase with a more obvious expression of oestrus. The ability to express oestrus has a low heritability and an unfavourable genetic correlation to milk production. Therefore it is very important to have good recordings of this trait and to consider the trait when breeding for increased milk production.